Glazed tile, porous glazed tile and preparation method
By using red soil powder and sodium bicarbonate powder to prepare glazed tiles, mold extrusion, drying and single sintering methods, the problems of cumbersome processes and high energy consumption in the existing technology are solved, and the glazed tiles are smooth and bright and beautiful. Chemical stability.
Patent Information
- Application Number
- CN202411710066.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-18
AI Technical Summary
The existing glazed tiles are cumbersome in preparation, have high energy consumption, and require two sintering, which affects industrial production efficiency.
Glazed tiles or porous glaze tiles are prepared by mold extrusion, drying and single sintering to form a smooth, bright, smooth and flat glaze surface.
It simplifies the preparation process, reduces energy consumption, improves the finish and chemical stability of glazed tiles, and is suitable for industrial production.
Smart Images

Figure CN119462070A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a glazed tile or a porous glazed tile and also to a preparation method of the glazed tile or the porous glazed tile, belonging to the technical field of building materials. Background Art
[0002] Glazed tiles are made by applying glaze on the upper surface of bricks or brick blanks, and then sintering them at high temperature. Glazed tiles are composed of two parts: bricks and glaze on the upper surface. By changing the composition of the glaze, glazed tiles with completely different patterns and colors can be made. Glazed tiles, as building finishing materials, have the advantages of light weight, anti-fouling, and chemical corrosion resistance. In recent years, plastics, various fiber composite boards and other materials have been developed at home and abroad as finishing materials, but they cannot replace glazed tiles. On the contrary, they unexpectedly stimulated the growth of glazed tile production, especially for underground construction facilities, such as shopping malls, underground warehouses, entertainment venues, etc. It has the advantages of waterproof, fireproof, explosion-proof, etc., which are incomparable to plastics and various composite boards.
[0003] Unique characteristics of glazed tiles: (1) Glazed tiles have bright colors, diverse patterns, and beautiful appearance. They can be used for interior decoration, and consumers have a wide range of choices; (2) Glazed tiles have high surface strength, strong anti-seepage, anti-skid and anti-fouling capabilities, and wear resistance that can meet daily household needs; (3) Glazed tiles have low water absorption and are not easy to penetrate liquids. There is generally no cracking between the glaze and the body, and the glaze is not easy to fall off. (4) Resistance to rapid cooling and heating: Resistance to rapid cooling and heating refers to the property of glazed tiles that they can withstand rapid changes in temperature without cracking. The temperature difference between hot and cold used in the test is 130±2℃; (5) Bending strength: The average bending strength of glazed tiles is not less than 16MPa. When the thickness of the tile is greater than or equal to 7.5mm, the average bending strength is not less than 13MPa. Based on the unique characteristics of glazed tiles, they are widely used and are suitable for interior decoration such as living rooms, kitchens, restaurants, KTVs and bathrooms. Consumers can choose according to their personal decoration style and preferences.
[0004] Chinese patent CN106272899A discloses a method for producing glazed tiles, the production process of which is (1) pressing and forming, (2) biscuit firing, (3) biscuit dry polishing, (4) glazing and pattern decoration, (5) glaze firing, and finally obtaining the finished product. This production method has an additional key step, which is the third step of biscuit dry polishing. Multiple groups of dry polishing grinding heads are used to perform non-continuous multi-point curved surface grinding and polishing on the biscuit in sequence, which can eliminate the dirt, surface defects and protrusions caused by biscuit firing. In this way, the surface of the biscuit becomes smooth and flat, and the fluidity of the glaze on the biscuit is increased, making it more flat, thereby reducing the amount of glaze, glaze pits after glaze firing, pinholes and other glaze defects, and improving the quality of the glaze. However, the process of this method is cumbersome, and it needs to go through two sintering processes of biscuit firing and glaze firing, which consumes a lot of energy. Summary of the invention
[0005] In view of the defects of the preparation method of glazed tiles in the prior art, the first object of the present invention is to provide a preparation method of glazed tiles or porous glazed tiles, which has a simple operation process, a short flow, high energy consumption, and is conducive to industrial production. The glaze surface of the obtained glazed tiles or porous glazed tiles is bright and smooth, has a dense chemical structure and good chemical stability.
[0006] The second object of the present invention is to provide a glazed tile or porous glazed tile, the glaze surface of which is bright and beautiful, smooth and flat, with a compact chemical structure and good chemical stability.
[0007] In order to achieve the above technical objectives, the present invention provides a method for preparing glazed tiles or porous glazed tiles, which includes scheme A, scheme B or scheme C:
[0008] Scheme A: Add water to red soil powder and sodium bicarbonate powder and stir until uniform to obtain a mixture; after the mixture is allowed to stand for a period of time, it is extruded through a mold to obtain a green body; the green body is dried and sintered to obtain a glazed tile;
[0009] Scheme B: Add water to red soil powder and stir until evenly mixed to obtain a mixture; after the mixture is allowed to stand for a period of time, it is extruded through a mold to obtain a green body; after the green body is dried, sodium bicarbonate powder is evenly applied to its surface and sintered to obtain a glazed tile;
[0010] Solution C: Fill a portion of the red soil powder into a sponge, mix the other portion of the red soil powder into a thin mud, absorb it with the sponge filled with the red soil powder, dry it, and obtain a green body; after the green body is dried, evenly apply sodium bicarbonate powder on its surface, and sinter it to obtain a porous glazed tile.
[0011] The key point of the technical solution of the present invention in the process of preparing glazed tiles or porous glazed tiles is that red soil is used as the raw material of the brick body and sodium bicarbonate is used as an additive, and the mineral and element components contained in the red soil raw material itself are fully utilized to generate a glaze on the surface of the brick body under the induction of sodium bicarbonate during the high-temperature sintering process, and the main phase of the generated glaze is Sr2GeO4, which has a bright and smooth appearance, a compact chemical structure, and good chemical stability. In particular, the method is simple to operate, has low energy consumption, and is easy to obtain raw materials, avoiding the existing glazed tile preparation process that requires an independent additional glazing process on the brick body surface and requires two sintering processes.
[0012] As a preferred solution, in Solution A, the mass of the sodium bicarbonate powder is more than 8% of the mass of the red soil powder. When the mass of the sodium bicarbonate powder reaches 8% of the mass of the red soil powder, a glassy glaze is formed on the surface of the brick body, and as the amount of sodium bicarbonate powder added increases, the glassy glaze formed on the surface of the brick body will appropriately thicken, but it is not suitable to add too much sodium bicarbonate into the red soil. Therefore, the mass of the sodium bicarbonate powder is further preferably 8-12% of the mass of the red soil powder.
[0013] As a preferred solution, in solution B, the amount of sodium bicarbonate powder applied to the surface of the blank is not less than 440 g / m 2 When the amount of sodium bicarbonate powder applied on the surface of the blank reaches 440g / m 2 When the amount of sodium bicarbonate powder applied to the body surface is 440-800 g / m 2 .
[0014] As a preferred solution, in solution C, the amount of sodium bicarbonate powder applied to the surface of the blank is not less than 220 g / m 2 When the amount of sodium bicarbonate powder applied on the surface of the blank reaches 220g / m 2 When the amount of sodium bicarbonate powder applied to the body surface is 220-600 g / m2, a uniform glassy glaze can be formed on the surface of the brick, and as the amount of sodium bicarbonate powder applied to the body surface increases, the glassy glaze formed on the surface of the brick will become appropriately thicker. Therefore, the amount of sodium bicarbonate powder applied to the body surface is 220-600 g / m2. 2 .
[0015] As a preferred solution, the condition of the static treatment is: standing at room temperature for 12 to 36 hours.
[0016] As a preferred solution, in solution A, the drying process is as follows: the initial drying temperature is set at 25-35°C, the temperature is increased by 5-15°C every 24 hours, and when the surface of the green body is completely covered with white powder, the drying is continued at 100°C for 36-100 hours. Drying is performed under the preferred conditions so that sodium bicarbonate is uniformly precipitated on the surface of the green body, which is conducive to the uniform formation of the subsequent glaze.
[0017] As a preferred solution, in solution B or solution C, the drying process is: first air-dry for 12 to 36 hours, then set the initial drying temperature to 25 to 35°C, increase the temperature by 5 to 15°C every 24 hours, and continue drying at 100°C for 36 to 100 hours when the surface of the body is completely covered with white powder. Drying under the preferred conditions allows sodium bicarbonate to be uniformly precipitated on the surface of the body, which is conducive to the uniform formation of the subsequent glaze.
[0018] As a preferred solution, in Scheme A, Scheme B or Scheme C, the sintering conditions are: set the initial temperature to 200°C, and when the temperature is raised to 1050~1150°C at a heating rate of 20~30°C / h, continue sintering for 1~3h, and then cool with the furnace. During the sintering process, if the temperature is too low, the generated glaze surface is not smooth, flat and dense, such as there are many glaze pits, pinholes, etc., and the glaze thickness is also low. If the temperature is too high, a lot of energy is consumed. The starting temperature of the glazed tile blank fired in the muffle furnace is 200°C, and the color of the blank is light yellow. When the temperature is about 400°C, the color of the blank becomes dark black. When the temperature is about 600°C, the blank glows red and as the temperature rises, the red light becomes stronger and stronger. When the temperature is about 1100°C, the blank looks like a burning fireball.
[0019] Compared with the prior art, the technical solution of the present invention has the following beneficial technical effects:
[0020] The preparation method of the glazed tile or porous glazed tile of the present invention has simple operation process, short flow, high energy consumption and is conducive to industrial production.
[0021] The glaze surface of the glazed tile or porous glazed tile of the present invention is bright and beautiful in appearance, smooth and flat, has a compact chemical structure and good chemical stability.
[0022] The main phase composition of the glaze surface of the glazed tile or porous glazed tile of the present invention is Sr2GeO4, which has strong chemical corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is an infrared image of the glaze surface of the glazed tile prepared in Example 1.
[0024] Figure 2 This is the X-ray diffraction pattern of the glaze surface of the glazed tile prepared in Example 1.
[0025] Figure 3 This is the SEM morphology of the cross section of the glazed tile prepared in Example 1.
[0026] Figure 4 The actual pictures are of the glazed bricks (with added sodium bicarbonate) prepared in Example 1 and the ordinary bricks (without added sodium bicarbonate) prepared in Comparative Example 1, wherein the left one is the ordinary brick and the right one is the glazed brick.
[0027] Figure 5 The scanning electron microscope image of the glaze surface of the glazed tile prepared at 1000°C for comparison with Example 2 shows that there are many glaze pits and pinholes on its surface.
[0028] Figure 6This is a scanning electron microscope image of the glaze surface of the glazed tile prepared at 1100° C. in Example 2. It can be seen from the image that the surface is relatively smooth and flat. DETAILED DESCRIPTION
[0029] The following specific examples are intended to further illustrate the present invention rather than to limit the scope of protection of the claims.
[0030] The pretreatment of the red soil raw material involved in the following specific embodiments is as follows: the red soil raw material is crushed by a hammer and passed through a 40-mesh sieve to obtain red soil powder with a particle size less than 40 mesh.
[0031] The following specific embodiments involve structural performance analysis of brick materials:
[0032] Fourier transform infrared spectroscopy analysis: Use an infrared spectrometer to measure the infrared spectrum of the brick sample, with a scanning range of 400~4000cm -1 , first hammer the brick to be tested into powder, then grind it and use KBr to press it into a pellet for infrared analysis.
[0033] X-ray diffraction analysis: Rigaku D / Max 2500 X-ray diffractometer was used to perform phase analysis on the brick samples. The analysis conditions were as follows: the diffraction ray was Cu-Kα ray (λ=1.5406Ǻ), the scanning rate was 10o / min, the diffraction angle range was 10-80°, and the acceleration voltage and current were 15kV and 20mA respectively.
[0034] Scanning electron microscope analysis: The brick sample was placed in an ethanol solution and ultrasonically treated in an ultrasonic disperser for 20 min. A small amount of the suspension was dripped on a small glass piece and allowed to dry naturally. Finally, the glass piece with particles was placed on the sample stage and subjected to SEM observation after gold spraying.
[0035] Inductively coupled plasma mass spectrometer (ICPMS, X SERIES 2, USA) analysis: First, the brick sample is dissolved, and the atomizer will send the solution sample into the plasma light source. After vaporization, the ionized gas is dissociated. The ions collected by the copper or nickel sampling cone enter the quadrupole mass spectrometer through the interceptor plate, and after mass separation by the mass filter, they reach the ion detector. According to the ratio of the detector count to the concentration, the content of the element can be measured. The components of red soil are mainly salts and oxides. The metal elements are scanned and quantitatively analyzed by inductively coupled plasma mass spectrometer. The red soil mainly contains aluminum (Al), titanium (Ti) and zinc (Zn) and other metal elements, as shown in Table 1.
[0036]
[0037] Example 1
[0038] Preparation of glazed tiles:
[0039] (1) Use a small iron shovel to scoop red soil powder from a plastic basin and place it in a clean beaker. When the beaker reaches the mark of 500 ml, stop scooping and weigh the total weight on an electronic balance. Subtract the weight of the beaker to obtain a weight of 228.7 g of red soil powder. Pour it into a clean plastic basin.
[0040] (2) Place a clean small beaker on the electronic balance. When the reading stabilizes, press the self-calibration button and the reading will return to zero. Then use a medicine spoon to take out NaHCO3 powder from the reagent bottle and pour it into the small beaker. Accurately weigh 4.6 g of NaHCO3 powder (about 2% of the mass of the red soil). Then pour the weighed NaHCO3 powder into a plastic basin and mix it with the red soil powder.
[0041] (3) Wear a protective mask, and then use a digital display powerful electric stirrer to mix the red soil powder and NaHCO3 powder evenly. It should be noted that the gear of the digital display powerful electric stirrer cannot be adjusted too high, because the high-speed rotation of the stirrer will splash the red soil powder and NaHCO3 powder. After the two are mixed evenly, add an appropriate amount of water to the plastic basin. At this time, you can appropriately increase the gear of the digital display powerful electric stirrer, add water while stirring, stir for 1 hour, let it stand for 5 hours, then move it into the brick mold, use a knife and hand to squeeze it into a brick shape, then slowly separate the brick mold from the brick, and let the brick dry at room temperature.
[0042] (4) When the bricks are dry enough to be picked up by hand without deformation, place them in an electric blast drying oven, set the temperature to 30°C, and increase the temperature by 10°C every 24 hours. After the glazed bricks are completely dry, the surface will be covered with a layer of white powder, but the surface of the glazed bricks covered with white powder does not mean that the bricks are completely dry, and it is possible that the moisture inside has not evaporated completely. When the temperature of the electric ancient style drying oven is set to 100°C, take out the glazed bricks the next day and observe carefully. If the surface of the bricks is completely covered with white powder, continue drying at 100°C for 72 hours.
[0043] (5) Place the completely dried glazed tile blank at room temperature for 24 hours, measure its length, width and height with a ruler, and then move it into a muffle furnace for firing. The initial temperature is set to 200℃, and then the temperature is increased by 50℃ every 2 hours. When the temperature rises to 1100℃, continue firing for 2 hours, then turn off the power switch of the muffle furnace and keep the furnace door closed. After cooling naturally overnight, open the furnace door to accelerate cooling. When the temperature in the furnace drops below 100℃, use iron clips to clamp the glazed tile out and place it on an iron basin to let it cool naturally to room temperature.
[0044] Control experimental group: the mass ratio of NaHCO3 powder to red soil powder was changed to 4%, 6%, 8% and 10% respectively, and then the experimental steps of Example 1 were repeated to prepare 5 glazed tiles.
[0045] The main phase composition of glazed tiles is Sr2GeO4, among which titanium content is the highest. The thickness of the glaze is about 0.48mm. The surface of the brick is rough, but the glaze is smooth and flat, and the structure of the glaze is dense.
[0046] Effect of different NaHCO3 contents on glaze formation:
[0047] When the content of NaHCO3 powder in Example 1 is 2% of the mass of the red soil powder, the color of the glazed tiles is reddish brown; when the content of NaHCO3 is 4%, the color of the brick body is still reddish brown; when the content of NaHCO3 is 6%, the color of the brick body is dark wine red; when the content of NaHCO3 is 8%, a glassy glaze is formed on the surface of the brick body; when the content of NaHCO3 is 10%, a thicker glassy glaze is formed on the surface of the brick body.
[0048] Figure 1 The infrared spectrum of the glazed brick made by mixing the NaHCO3 powder with the red soil powder at 8% of its mass. -1 The antisymmetric stretching vibration of Si-O-Si is 779.51cm -1 The Si-O-Si symmetric stretching vibration is 901.78 cm -1 The position is Ge-O-Ge asymmetric stretching vibration, 699.06cm -1 The region is the bending vibration of the Ge-O-Ge bond.
[0049] X-ray diffraction pattern analysis: Figure 2 The X-ray diffraction pattern of the glazed tile made by mixing the NaHCO3 powder in Example 1, which is 8% of the mass of the red soil powder. The X-ray diffraction pattern of the glazed surface has no diffraction peaks, indicating that the substance is an amorphous body or a glass body, which is non-crystalline. The analysis software jade5.0 is used to conduct a deeper analysis of the spectrum, and it is known that the main phase composition of the glaze is Sr2GeO4. The main phase composition of the particles inside the glazed tile is BPO4 and SiO2, and its relative crystallinity is 24.36%.
[0050] Depend on Figure 3 It can be seen that there is an obvious dividing line between the glaze and the brick body. It can be seen that the thickness of the glaze is 0.35~0.55mm. The surface of the brick body is rough, but the glaze is smooth and flat, indicating that the structure of the glaze is dense.
[0051] Chemical corrosion resistance test:
[0052] (1) Soak the glazed tiles in a 6% NaOH solution for 12 hours. After the test, take out the glazed tiles, rinse them with water, wipe them dry, and then compare them with the reference. It is found that there is no obvious change in the glaze surface.
[0053] (2) The glazed tiles were immersed in a 6% HCl solution for 12 hours. After the test, the glazed tiles were taken out, rinsed with water, wiped dry, and then compared with the reference. No obvious changes were found on the glaze surface.
[0054] Example 2
[0055] Preparation of glazed tiles:
[0056] (1) Place a piece of weighing paper on the electronic analytical balance. After the reading stabilizes, press the zero button and the reading will return to zero. Then use a medicine spoon to take out NaHCO3 powder from the reagent bottle and gently pour it onto the weighing paper. Accurately weigh 1.0075 g of NaHCO3 powder.
[0057] (2) Spread the weighed NaHCO3 powder on the upper surface of a completely dried ordinary brick blank (the brick blank preparation method is specifically referred to Comparative Example 1) whose length, width and height have been measured, and then move it into a muffle furnace for firing. The initial temperature is set to 200°C, and then the temperature is increased by 50°C every 2 hours. When the temperature rises to 1100°C, continue firing for 2 hours and then stop the furnace. Keep the furnace door closed. After cooling naturally overnight, open the furnace door to accelerate cooling. When the temperature in the furnace drops below 100°C, use iron clamps to clamp the glazed tiles out and place them on an iron basin to allow them to cool naturally to room temperature.
[0058] Control experimental group: the mass of NaHCO3 powder was changed to 2.0021g, 3.0036g, 4.0028g and 5.0043g respectively, and then the above experimental steps were repeated to prepare 5 glazed tiles.
[0059] Effect of different NaHCO3 contents on glaze formation:
[0060] The upper surface area is 66.93 cm 2When 1.0075g of NaHCO3 powder was spread on an ordinary brick blank, the upper surface of the fired brick was dark wine red; when the mass of NaHCO3 was 2.0021g, a glassy glaze was formed on part of the upper surface of the brick, and the rest was dark wine red; when the mass of NaHCO3 was 3.0036g, the upper surface of the brick was covered with a layer of glassy glaze; when the mass of NaHCO3 was 4.0028g, the upper surface of the brick was covered with a thicker layer of glassy glaze, and glassy glaze was also formed on its side; when the mass of NaHCO3 was 5.0043g, not only was the upper surface of the brick covered with a thicker layer of glassy glaze, but more glassy glaze was also formed on its side.
[0061] Example 3
[0062] Preparation of porous glazed tiles:
[0063] (1) Place a piece of weighing paper on the electronic analytical balance. After the reading stabilizes, press the zero button and the reading will return to zero. Then use a medicine spoon to take out the NaHCO3 powder from the reagent bottle and gently pour it onto the weighing paper. Accurately weigh 0.5034 g of NaHCO3 powder.
[0064] (2) Spread the weighed NaHCO3 powder on the upper surface of a porous brick blank that has been completely dried and whose length, width and height have been measured (the preparation method of the brick blank refers to Comparative Example 2), and then move it into a muffle furnace for firing. The initial temperature is set to 200°C, and the temperature is increased by 50°C every 2 hours. When the temperature rises to 1100°C, continue sintering for 2 hours and then stop the furnace. Keep the furnace door closed. After cooling naturally overnight, open the furnace door to accelerate cooling. When the temperature in the furnace drops below 100°C, use iron clamps to clamp the porous glazed bricks out and place them on an iron basin to allow them to cool naturally to room temperature.
[0065] The mass of NaHCO3 powder was changed to 1.0008g, 1.5073g, 2.0019g and 2.5025g respectively, and then the above experimental steps were repeated to prepare five porous glazed tiles.
[0066] Preparation of porous glazed tiles: The upper surface area is 45.6cm 2When 0.5034g of NaHCO3 powder was spread on an ordinary porous brick blank, the color of the upper surface of the fired porous glazed tile was dark wine red; when the mass of NaHCO3 was 1.0008g, a glassy glaze was formed on part of the upper surface of the brick, and the rest was dark wine red; when the mass of NaHCO3 was 1.5073g, a glassy glaze was formed on the upper surface of the brick; when the mass of NaHCO3 was 2.0019g, the upper surface of the brick was covered with a thicker layer of glassy glaze; when the mass of NaHCO3 was 2.5025g, not only was the upper surface of the brick covered with a thicker layer of glassy glaze, but glassy glaze was also formed on its sides.
[0067] Comparative Example 1
[0068] Preparation of ordinary bricks:
[0069] (1) Use a small iron shovel to scoop red soil powder from the plastic basin into a clean beaker. Stop scooping when the beaker reaches the mark of 500 mL. Weigh the total weight of the beaker and red soil powder on an electronic balance to be 296 g. Then slowly pour the red soil powder in the beaker into the clean plastic basin. The pouring action must be gentle and slow. If it is too fast, the red soil powder will float everywhere. Weigh the mass of the empty beaker again to be 63.8 g, and the weight of the red soil powder is 296-63.8=232.2 g.
[0070] (2) Add an appropriate amount of water to a plastic basin and turn on a digital high-power electric stirrer, stirring while adding water. After sufficient water is added, continue stirring for 1 hour, then let it stand for 5 hours, then transfer the sludge into a brick mold, use a knife and hands to squeeze it into a brick shape, then slowly separate the brick mold from the brick, and let the brick dry at room temperature.
[0071] (3) When the bricks are dry enough to be picked up by hand without deformation, place them in an electric blast drying oven, set the temperature to 30°C, and increase the temperature by 10°C every 24 hours. Ordinary bricks with more water content are reddish brown in color, while bricks with very little water content are light yellow. It should be noted that when the color of the bricks is light yellow, it does not mean that they are completely dry. It is possible that only the surface is completely dry and there is more water inside. When the temperature of the electric ancient style drying oven is set to 100°C, take out the bricks the next day and observe them carefully. If the color is all light yellow, continue drying at 100°C for 72 hours.
[0072] (4) Place the completely dried bricks at room temperature for 24 hours, measure their length, width and height with a ruler, and then move them into a muffle furnace for firing. Set the initial temperature to 200°C, and increase the temperature by 50°C every 2 hours. When the temperature rises to 1100°C, continue sintering for 2 hours and then stop the furnace. Keep the furnace door closed. After cooling naturally overnight, open the furnace door to accelerate cooling. When the temperature in the furnace drops below 100°C, use iron clips to take out ordinary bricks and place them on an iron basin to let them cool naturally to room temperature. It should be noted that bricks that have not been completely dried must not be placed in a muffle furnace for firing, otherwise the bricks containing more water will expand rapidly and burst and scatter at high temperatures.
[0073] Then repeat the experimental steps of comparative example 1 to prepare five ordinary bricks, and the surface of the bricks is not glazed. The comparison between the glazed bricks prepared by the same firing process (to 1100°C) and the ordinary bricks is shown in Figure 4 , the left side of the picture is ordinary brick, and the right side is glazed brick.
[0074] Comparative Example 2
[0075] Preparation of porous bricks:
[0076] (1) Cut the sponge with a knife to obtain a sponge strip with a length, width and height of 8.0 cm, 5.7 cm and 2.0 cm respectively. Then place it in an iron basin covered with red soil powder. Use a small iron shovel to scoop the red soil powder and pour it on the upper surface of the sponge to cover it completely. Then use the small iron shovel to gently tap the sponge. Some of the red soil powder will then sink into the sponge, and some will fall onto the iron basin. It should be noted that the force of the tapping should not be too strong. There are two reasons for this: one is to prevent the red soil powder from flying; the other is that the red soil powder that has entered the sponge will be easily knocked out. Use a small iron shovel to scoop the red soil powder onto the sponge and continue tapping. Repeat this process until the red soil powder is filled to saturation.
[0077] (2) Use a small iron shovel to scoop an appropriate amount of red soil powder into a plastic basin, add an appropriate amount of water to make a thin mud, and rub it with your hands for 0.5 hours. Then put the sponge filled with red soil powder on the thin mud, and gently squeeze the sponge with your hands. The thin mud will be absorbed into it. After continuous squeezing for 0.5 hours, it can be made into a porous brick blank, and then placed at room temperature to dry naturally for 24 hours. It should be noted that too much water should not be added. If there is too much water, the red soil powder will be squeezed out easily during the squeezing of the sponge.
[0078] (3) The next day, move the porous bricks into an electric forced air drying oven for drying. Set the temperature to 30°C and increase the temperature by 10°C every 24 hours. When the temperature of the electric forced air drying oven is set to 100°C, maintain the current temperature and continue drying for 72 hours.
[0079] (4) Place the completely dried porous brick blank at room temperature for 24 hours, and measure its length, width and height with a ruler. Move it into a muffle furnace for firing the next day. The initial temperature is set to 200°C, and the temperature is increased by 50°C every 2 hours. When the temperature rises to 1100°C, continue firing for 2 hours and then stop the furnace. Keep the furnace door closed. After cooling naturally overnight, open the furnace door to accelerate cooling. When the temperature in the furnace drops below 100°C, use an iron clamp to clamp the porous brick out and place it on an iron basin to let it cool naturally to room temperature. Repeat the above experimental steps to prepare 5 porous bricks with no glaze on the surface.
[0080] Comparative Example 3
[0081] Compared with Example 2, the only difference is that the sintering temperature is lowered to 1000°C.
[0082] Element analysis: Sample No. 1 in Table 2 is the glaze fired in Comparative Example 3, Sample No. 2 is the glaze fired in Example 2, and Sample No. 3 is the glaze fired in Example 1. In the process of dissolving the samples, it was found that the samples were difficult to dissolve or even did not dissolve, resulting in the absence of strontium, germanium and oxygen in the test result table, but this indirectly shows that the structure of the glaze is very stable.
[0083]
[0084] Scanning electron microscopy analysis: Figure 5 It can be seen that the glaze surface fired at 1000°C using Comparative Example 2 has many glaze pits and pinholes. Figure 6 It can be seen that the surface of the glaze fired at 1100°C in Example 2 is relatively smooth and flat, indicating that the quality of the glaze fired at 1100°C is better.
Claims
1. A method for preparing a glazed tile or a porous glazed tile, characterized in that: Includes Plan A, Plan B or Plan C: Scheme A: Add water to red soil powder and sodium bicarbonate powder and stir until uniform to obtain a mixture; after the mixture is allowed to stand for a period of time, it is extruded through a mold to obtain a green body; the green body is dried and sintered to obtain a glazed tile; Scheme B: Add water to red soil powder and stir until evenly mixed to obtain a mixture; after the mixture is allowed to stand for a period of time, it is extruded through a mold to obtain a green body; after the green body is dried, sodium bicarbonate powder is evenly applied to its surface and sintered to obtain a glazed tile; Solution C: Fill a portion of the red soil powder into a sponge, mix the other portion of the red soil powder into a thin mud, absorb it with the sponge filled with the red soil powder, dry it, and obtain a green body; after the green body is dried, evenly apply sodium bicarbonate powder on its surface, and sinter it to obtain a porous glazed tile.
2. The method for preparing a glazed tile or porous glazed tile according to claim 1, characterized in that: In scheme A, the mass of the sodium bicarbonate powder is more than 8% of the mass of the red soil powder.
3. The method for preparing a glazed tile or porous glazed tile according to claim 1, characterized in that: In scheme B or scheme C, the amount of sodium bicarbonate powder applied to the surface of the blank is not less than 440g / m 2 .
4. The method for preparing a glazed tile or porous glazed tile according to claim 1, characterized in that: The condition of the static treatment is: standing at room temperature for 12 to 36 hours.
5. The method for preparing a glazed tile or porous glazed tile according to claim 1, characterized in that: In scheme A, the drying process is as follows: the initial drying temperature is set at 25-35°C, the temperature is increased by 5-15°C every 24 hours, and when the surface of the green body is completely covered with white powder, the green body is dried at 100°C for 36-100 hours.
6. The method for preparing a glazed tile or porous glazed tile according to claim 1, characterized in that: In Scheme B or Scheme C, the drying process is: first naturally air-dry for 12 to 36 hours, then set the initial drying temperature to 25 to 35°C, increase the temperature by 5 to 15°C every 24 hours, and when the surface of the blank is completely covered with white powder, continue drying at 100°C for 36 to 100 hours.
7. The method for preparing a glazed tile or porous glazed tile according to claim 1, characterized in that: In Scheme A, Scheme B or Scheme C, the sintering conditions are: setting the initial temperature to 200°C, heating at a rate of 20-30°C / h, heating to 1050-1150°C, continuing sintering for 1-3h, and then cooling with the furnace.
8. A glazed tile or porous glazed tile, characterized in that: Obtained by the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Glazed tile production method
CN106272899A